The results of efficacy evaluation of colostomy and devices for sealing the rectum in patients with anaerobic paraproctitis - K.I. Sergatskiy; V.I. Nikol'skiy; E.V. Titova; V.E. Kiselev; Ya.E. Feoktistov; A.V. Gerasimov (Известия высших учебных заведений. Поволжский регион: Медицинские науки, 2021)
Background. An important factor in creating conditions for the healing of perineal wounds after opening and surgical debridement of the focus of infection in patients with acute paraproctitis is the fight against contamination with the contents of the rectum. There are 2 options for solve the problem − the removal of a protective colostomy and the use of special devices for sealing the rectum and controlled removal of feces. However, there is no assessment of the effectiveness of these techniques in patients with acute anaerobic paraproctitis. The purpose of this research is to develop a set of measures to prevent the contamination of extensive perineal wounds with fecal masses in patients with acute anaerobic paraproctitis. Materials and methods. We studied 71 cases of acute anaerobic paraproctitis during the study period. In 3 patients (4.2%), pronounced destruction of the rectal wall above the level of the dentate line was revealed, which served as an indication for the imposition of a protective double-barreled sigmostomy. To prevent contamination of the wound surface of the perineum with the contents of the colon in 11 (15.5%) patients with acute anaerobic paraproctitis, a device was used that provided the removal of feces. Results. The calculation and comparison of the density of microbial colonization of the postoperative wound, the leukocyte index of intoxication, the level of C-reactive protein and some clinical parameters in patients, depending on the method used to prevent contamination of the wound surface with the contents of the colon, was carried out. Conclusions. In patients with acute anaerobic paraproctitis, in the presence of extensive wound surfaces, for the prevention of contamination of postoperative wounds, the method of choice is the use of special devices for controlled removal of feces. Protective colostomy can be used in exceptional cases − with total destruction of all walls of the rectum above the level of the dentate line and in the absence of the technical possibility of using special devices for controlled fecal removal.